2005
DOI: 10.1111/j.0959-9673.2005.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

The haemotoxicity of mitomycin in a repeat dose study in the female CD‐1 mouse

Abstract: Mitomycin (MMC), like many antineoplastic drugs, induces a predictable, dose-related, bone marrow depression in man and laboratory animals; this change is generally reversible. However, there is evidence that MMC may also cause a late-stage or residual bone marrow injury. The present study in female CD-1 mice investigated the haematological and bone marrow changes induced by MMC in a repeat dose study lasting 50 days. Control and MMC-treated mice were dosed intraperitoneally on eight occasions over 18 days wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 65 publications
5
22
0
Order By: Relevance
“…Histological assessment of the spleen (Gibson et al 2003) demonstrated reduced haemopoietic activity in the red pulp, with only slight erythropoiesis, myelopoiesis and megakaryopoiesis. Furthermore, in a study with mitomycin in the mouse (Molyneux et al 2005), spleen relative weights were reduced to 50.6% of control at day 1 post-dosing, and here, histopathology showed a reduction in the cellularity of the red pulp (i.e. reduced haematopoiesis).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Histological assessment of the spleen (Gibson et al 2003) demonstrated reduced haemopoietic activity in the red pulp, with only slight erythropoiesis, myelopoiesis and megakaryopoiesis. Furthermore, in a study with mitomycin in the mouse (Molyneux et al 2005), spleen relative weights were reduced to 50.6% of control at day 1 post-dosing, and here, histopathology showed a reduction in the cellularity of the red pulp (i.e. reduced haematopoiesis).…”
Section: Discussionmentioning
confidence: 51%
“…The second (theoretical) approach would involve the administration of a first BU regimen (ten doses, 9.0 mg/kg over 21 days), entry into the plateau phase from about day 50 post-dosing, followed by the administration of a second drug regimen, with a different agent, also known to induce late-stage/residual marrow injury. To identify such a second drug, investigations with CHB, MIT-C and azathioprine have been carried out (Molyneux et al 2004(Molyneux et al , 2005(Molyneux et al , 2008. Therefore, to progress to this second approach, the need has now arisen to develop a convenient shortterm method for identifying (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, fever and weight loss were not induced in SFTSV-infected C57/BL6 mice (Table 1), and all tested mice survived. To evaluate if the immunocompromised animals could develop a more severe disease and even fatal outcome, we used immunosuppressive drug mitomycin C, which is known to inhibit the hematopoiesis in bone marrow (5), to treat SFTSV-infected mice. We found that with mitomycin C application, 50% of the SFTSV-infected mice died between day 9 and day 10, and the remaining surviving mice experienced a significant loss of body mass compared with uninfected mice administered mitomycin C in parallel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some HUS animal models rely on the manipulation of the intestinal environment with different drugs such as antibiotics (Lindgren et al, 1993;Wadolkowski et al, 1990) or mitomycin C (Fujii et al, 1994) in order to establish reproducible infections. However, these treatments could disturb the immune response of the host (Domingo et al, 1995), alter Stx excretion (Grif et al, 1998) or induce microangiopathy (Molyneux et al, 2005).…”
Section: Introductionmentioning
confidence: 99%